In Vitro blood-brain barrier models for neuroinfectious diseases: a narrative review - Badawi, Ahmad Hussein; Mohamad, Nur Afiqah; Stanslas, Johnson; Kirby, Brian Patrick; Neela, Vasantha Kumari; Ramasamy, Rajesh; Basri, Hamidon (Bentham Science Publishers, 2024)
The blood-brain barrier (BBB) is a complex, dynamic, and adaptable barrier between the peripheral blood system and the central nervous system. While this barrier protects the brain and spinal cord from inflammation and infection, it prevents most drugs from reaching the brain tissue. With the expanding interest in the pathophysiology of BBB, the development of in vitro BBB models has dramatically evolved. However, due to the lack of a standard model, a range of experimental protocols, BBB-phenotype markers, and permeability flux markers was utilized to construct in vitro BBB models. Several neuroinfectious diseases are associated with BBB dysfunction. To conduct neuroinfectious disease research effectively, there stems a need to design representative in vitro human BBB models that mimic the BBB's functional and molecular properties. The highest necessity is for an in vitro standardised BBB model that accurately represents all the complexities of an intact brain barrier. Thus, this in-depth review aims to describe the optimization and validation parameters for building BBB models and to discuss previous research on neuroinfectious diseases that have utilized in vitro BBB models. The findings in this review may serve as a basis for more efficient optimisation, validation, and maintenance of a structurally and functionally intact BBB model, particularly for future studies on neuroinfectious diseases.